The Influence of Flexible Working Space and Work-Life Balance on Employee Performance with Gender as Moderation - Ihtada Yogaisty; Herri Herri; Hendra Lukito (Budapest International Research and Critics University, 2022)
This study aims to analyze the effect of FWS and WLB on the performance of the DGSAM employees moderated by gender. This research is explanatory quantitative research. The data analysis technique used Partial Least Square. The number of respondents amounted to 385 people who are official civil servants of DGSAM. The results of this study found: that (1) FWS has a positive significant effect on employee performance. WLB which has 4 dimensions produces findings: (2a) Work Interference with Personal Life (WIPL) has a positive significant effect on Employee Performance, (2b) Personal Life Interference with Work (PLIW) has a negative significant effect on Employee Performance. (2c) Personal Life Enhancement of Work (PLEW) has a positive significant effect on employee performance. (2d) Work Enhancement of Personal Live (WEPL) has a positive significant effect on Employee Performance. Gender, which is the moderating variable in the relationship between FWS and WLB on Employee Performance, results in the following findings: (3) Gender doesn't moderate the relationship between FWS and Employee Performance. (4) Gender partially moderates the relationship between WLB and Employee Performance. The magnitude of the effect of FWS and WLB on Employee Performance is indicated by R² of 37.6%.